Organization of distance education for practical pharmacist at the faculty of postgraduate education - Mykhkailiuk, Ye. O.; Михайлюк, Євгеній Олегович (Manchester : Cognum Publishing House, 2022)
Medical and pharmaceutical universities must have the tools and technologies to enable distance education. Pharmacists must constantly improve their professional knowledge and practical skills, and the educational process should not distract them from their professional activities, for this postgraduate universities must use distance education with various digital technologies. The digital transformation of education needs to be carried out with care to maintain good connections between teachers and teachers, a sense of belonging and responsibility to the learning community, and substantial feedback. We need to make strategic decisions in order to adopt a new way of life, to be disciplined and focused in our practice, to be open to learning and to be able to prosper in the future.
Keywords: distance education; postgraduare education; pharmacy